Management of Moral and Systemic Institutions Based on Islamic School Culture - Muthmainnah, Fadkhuli; Joko Raharjo, Tri; Khafid, Muhammad (Educational Management, 2021)
Islamic school culture basically embodies daily activities based on Islamic guidelines. SD Islam Sultan Agung 01 Semarang is a school that implements management based on school culture. The purpose of this study is to describe and analyze the implementation and evaluation of the management of moral and systemic institutions based on Islamic school culture at SD Islam Sultan Agung 01 Semarang. This study approach is qualitative with the form of case studies. Data were collected through observation, interviews, and document studies. The data that has been collected is then analyzed using qualitative analysis, which is the results of the research that will be translated into words so that the researcher can describe the results of the research in depth according to the actual conditions in the field. The results of this study at SD Islam Sultan Agung 01 Semarang show that the management of moral and systemic institutions based on Islamic school culture includes: (1) implementation with process stages: MLBS program material, MLBS program strategy, and MLBS program implementation schedule, (2) evaluation in the form of process evaluation and result evaluation.